Adhesive composition and connection structure

By using conductive particles with Pd or Au layers in anisotropic conductive adhesives for connecting circuit members with Cu or Ag layers, the solution addresses the issue of unreliable connections over time, achieving enhanced reliability and longevity.

JP2025060847APending Publication Date: 2025-04-10RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024229070
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2024-12-25
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing connection methods using anisotropic conductive adhesives fail to maintain reliable electrical connections over time when connecting circuit members with Cu or Ag layers on their outermost surfaces.

Method used

A connection structure and adhesive composition that utilize conductive particles with a Pd or Au layer on their surface, paired with circuit members having Cu or Ag layers on their electrodes, to enhance electrical connection reliability.

Benefits of technology

The proposed solution achieves a more reliable and long-lasting electrical connection between circuit members with Cu or Ag layers, improving connection reliability compared to traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060847000001_ABST
    Figure 2025060847000001_ABST
Patent Text Reader

Abstract

To achieve a more reliable electrical connection when a circuit member having an electrode with a layer formed of Cu or Ag on the outermost surface is connected with an adhesive containing conductive particles.SOLUTION: A connection structure includes a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion provided between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein at least one of the first electrode and the second electrode has a layer formed of Cu or Ag on its outermost surface, and the connection portion contains conductive particles having a layer formed of Pd or Au on its outermost surface.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition and a connection structure. [Background technology]

[0002] In recent years, electronic components have become smaller, thinner, and more powerful, and high-density mounting technology has been actively developed. In such high-density mounting, it is difficult to connect circuit members having fine circuit electrodes using conventional solder and rubber connectors. Therefore, a connection method using anisotropic conductive adhesives and their films with excellent resolution is widely used. In this connection method, for example, when connecting a flexible printed circuit (FPC) to a glass substrate of a liquid crystal display, anisotropic conductive adhesive films containing conductive particles are sandwiched between opposing electrodes, and heated and pressed to bond and fix the circuit members to each other, and to electrically connect the electrodes of both circuit members while maintaining the insulation between adjacent electrodes on the same circuit member.

[0003] As an example of conductive particles used in the above-mentioned anisotropic conductive adhesive, Patent Document 1 discloses conductive particles having a metal layer formed on the surface of a film-forming particle, the metal layer having a Vickers hardness (Hv) of 35 to 400 and a thickness of 5 to 250 nm. The metal layer formed on the surface of the conductive particle is made of at least one metal material selected from the group consisting of copper (Cu), aluminum (Al), nickel (Ni), titanium (Ti), and ruthenium (Ru). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-181511 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, according to the inventors' investigations, it was found that when the outermost surface of the electrode to be connected is composed of a layer formed of Cu or Ag, even if an adhesive containing conductive particles as disclosed in Patent Document 1 is used, a good connection can be obtained initially, but the connection cannot be maintained over a long period of time (the connection reliability becomes insufficient).

[0006] Therefore, an object of the present invention is to obtain a more reliable electrical connection when a circuit component having an electrode with a layer formed of Cu or Ag on its outermost surface is connected with an adhesive containing conductive particles. [Means for solving the problem]

[0007] One aspect of the present invention is a connection structure comprising a first circuit member having a first electrode, a second circuit member having a second electrode, and a connection portion provided between the first circuit member and the second circuit member and electrically connecting the first electrode and the second electrode to each other, wherein at least one of the first electrode and the second electrode has a layer formed of Cu or Ag on its outermost surface, and the connection portion contains conductive particles having a layer formed of Pd or Au on its outermost surface.

[0008] Another aspect of the present invention is an adhesive composition that contains an adhesive component and conductive particles and is used to adhere a first circuit member having a first electrode and a second circuit member having a second electrode to each other and electrically connect the first electrode and the second electrode to each other, wherein the conductive particles have a layer formed of Pd or Au on their outermost surface, and at least one of the first electrode and the second electrode has a layer formed of Cu or Ag on their outermost surface.

[0009] In each of the above aspects, the conductive particles may have a layer formed of Pd on the outermost surface. Effect of the Invention

[0010] According to the present invention, when circuit components having an electrode with a layer formed of Cu or Ag on the outermost surface are connected with an adhesive containing conductive particles, a more reliable electrical connection can be obtained. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a cross-sectional view illustrating an embodiment of an adhesive composition. [Diagram 2] FIG. 1 is a cross-sectional view illustrating a schematic diagram of an embodiment of a conductive particle. [Diagram 3] 1A to 1C are cross-sectional views that diagrammatically show an embodiment of a method for manufacturing a connection structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings as needed. In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In addition, the upper limit and lower limit values ​​individually described can be arbitrarily combined. In addition, in this specification, "(meth)acrylate" means at least one of acrylate and the corresponding methacrylate. The same applies to other similar expressions such as "(meth)acryloyl". However, the present invention is not limited to the following embodiments.

[0013] The adhesive composition according to one embodiment is an adhesive film formed into a film shape. In another embodiment, the adhesive composition may be in a state other than a film shape (for example, a paste shape).

[0014] Fig. 1 is a cross-sectional view that shows a schematic diagram of a film-like adhesive composition (adhesive film) according to one embodiment. As shown in Fig. 1, in one embodiment, the adhesive film 1 includes an adhesive component 2 and conductive particles 3 dispersed in the adhesive component 2. The thickness of the adhesive film 1 may be, for example, 10 µm or more and 50 µm or less.

[0015] In one embodiment, the adhesive component 2 has insulating properties and contains a curable component that is cured by heat or light. The adhesive component 2 is defined as the components other than the conductive particles in the adhesive composition.

[0016] The hardenable component may include a polymerizable compound and a polymerization initiator, may include a thermosetting resin, or may include a polymerizable compound, a polymerization initiator, and a thermosetting resin.

[0017] The polymerizable compound may be, for example, a radically polymerizable compound. The radically polymerizable compound is a compound having a functional group that is polymerized by a radical. Examples of the radically polymerizable compound include (meth)acrylate compounds and maleimide compounds. The polymerizable compound is used alone or in combination of two or more. The content of the polymerizable compound may be, for example, 50% by mass or more and 80% by mass or less based on the total amount of the adhesive components.

[0018] Examples of the (meth)acrylate compound include urethane (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dimethylol tricyclodecane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, 2-hydroxy-1,3-di(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, tetramethylolpropane tri ... Examples of the methacryloxypropane include 2,2-bis[4-((meth)acryloxymethoxy)phenyl]propane, 2,2-bis[4-((meth)acryloxypolyethoxy)phenyl]propane, dicyclopentenyl(meth)acrylate, tricyclodecanyl(meth)acrylate, bis((meth)acryloxyethyl)isocyanurate, ε-caprolactone-modified tris((meth)acryloxyethyl)isocyanurate, tris((meth)acryloxyethyl)isocyanurate, and 2-(meth)acryloyloxyethyl acid phosphate. From the viewpoint of adhesiveness, the radical polymerizable compound may contain urethane(meth)acrylate.

[0019] The viscosity of the polymerizable compound at 25° C. may be 100,000 mPa·s or more, or may be 1,000,000 mPa·s or less, or 500,000 mPa·s or less. The viscosity of the polymerizable compound can be measured using a commercially available E-type viscometer.

[0020] The polymerization initiator may be, for example, a radical polymerization initiator. The radical polymerization initiator is a compound that decomposes by heating or light to generate free radicals, such as a peroxide compound or an azo compound. The polymerization initiator is appropriately selected depending on the intended connection temperature, connection time, pot life, etc. The content of the polymerization initiator may be, for example, 0.05% by mass or more and 15% by mass or less based on the total amount of the adhesive components.

[0021] The radical polymerization initiator may be, for example, one or more selected from benzoyl peroxide, diacyl peroxide, peroxydicarbonate, peroxy ester, peroxyketal, dialkyl peroxide, and hydroperoxide. From the viewpoint of high reactivity and pot life, the radical polymerization initiator may be an organic peroxide having a half-life of 10 hours of 40°C or higher and a half-life of 1 minute of 180°C or lower. The radical polymerization initiator may be used in combination with a decomposition accelerator, an inhibitor, etc. The polymerization initiator may be used alone or in combination of two or more.

[0022] Examples of the thermosetting resin include epoxy resin, cyanate ester resin, maleimide resin, allylnadimide resin, phenol resin, urea resin, melamine resin, alkyd resin, acrylic resin, unsaturated polyester resin, diallyl phthalate resin, silicone resin, resorcinol formaldehyde resin, xylene resin, furan resin, polyurethane resin, ketone resin, triallyl cyanurate resin, polyisocyanate resin, resin containing tris(2-hydroxyethyl)isocyanurate, resin containing triallyl trimellitate, thermosetting resin synthesized from cyclopentadiene, thermosetting resin by trimerization of aromatic dicyanamide, etc. The thermosetting resin may be used alone or in combination of two or more. The content of the thermosetting resin may be, for example, 20% by mass or more and 50% by mass or less based on the total amount of the adhesive component.

[0023] When the adhesive component contains a thermosetting resin, the adhesive component may further contain a curing agent. The curing agent may be melamine and its derivatives, hydrazide-based curing agents, boron trifluoride-amine complexes, sulfonium salts, aminimides, diaminomaleonitrile, polyamine salts, dicyandiamide, or the like, or modified products thereof. The curing agent may be a polyaddition-type curing agent such as polyamine, polymercaptan, polyphenol, or acid anhydride, or may be used in combination with a polyaddition-type curing agent and a catalyst-type curing agent. The curing agent may be used alone or in combination of two or more. The content of the curing agent may be, for example, 0.5% by mass or more and 15% by mass or less based on the total amount of the adhesive component.

[0024] The adhesive component may further contain a polymerization inhibitor. The polymerization inhibitor may be hydroquinone, methyl ether hydroquinone, etc. The content of the polymerization inhibitor may be, for example, 0.05% by mass or more and 5% by mass or less based on the total amount of the adhesive component.

[0025] The adhesive component may further contain a filler such as silica particles, a softener, an accelerator, an antioxidant, a colorant, a flame retardant, a thixotropic agent, a coupling agent, and the like.

[0026] When the adhesive composition is formed into a film, the adhesive component may further contain a thermoplastic resin to improve film formability. Examples of the thermoplastic resin include polystyrene, polyethylene, polyvinyl butyral, polyvinyl formal, polyimide, polyamide, polyester, polyvinyl chloride, polyphenylene oxide, urea resin, melamine resin, phenol resin, xylene resin, epoxy resin, polyisocyanate resin, phenoxy resin, polyimide resin, polyester urethane resin, polyurethane resin, etc.

[0027] The thermoplastic resin is preferably an epoxy resin or a phenoxy resin, and from the viewpoint of further improving connection reliability, it may be an epoxy resin or a phenoxy resin having a weight average molecular weight of 10,000 or more as determined by high performance liquid chromatography (HPLC). The adhesive component may contain a resin obtained by modifying these resins with a radically polymerizable functional group. The adhesive component may contain a styrene-based resin or an acrylic resin in addition to these resins for the purpose of adjusting the melt viscosity, etc.

[0028] FIG. 2 is a cross-sectional view showing an embodiment of a conductive particle 3 contained in an adhesive film 1. As shown in FIG. 2(a), a conductive particle 3A according to an embodiment has a substantially spherical polymer particle 31, a first metal layer 32A provided on the polymer particle 31, and a second metal layer 33A provided on the first metal layer 32A. The conductive particle 3A may be substantially spherical. It is preferable that substantially the entire surface of the polymer particle 31 is covered with the first metal layer 32A and the second metal layer 33A, but a part of the surface of the polymer particle 31 may be exposed without being covered with the first metal layer 32A and the second metal layer 33A, as long as the function of electrically connecting the circuit members is maintained.

[0029] The polymer particles 31 may be particles containing a polymer containing at least one monomer selected from styrene and divinylbenzene as a monomer unit. The polymer may further contain (meth)acrylate as a monomer unit.

[0030] The average particle size (diameter) of the polymer particles 31 may be preferably 1 μm or more and 40 μm or less. From the viewpoint of high-density mounting, the average particle size (diameter) of the polymer particles 31 may more preferably be 1 μm or more and 30 μm or less. From the viewpoint of maintaining a more stable connection state when there is variation in the surface unevenness of the electrodes, the average particle size (diameter) of the polymer particles 31 may further preferably be 2 μm or more and 20 μm or less.

[0031] The first metal layer 32A is formed of, for example, Ni, Cu, NiB, Ag, or Ru, and is preferably formed of Ni. The thickness of the first metal layer 32A may be, for example, 50 nm or more and 300 nm or less.

[0032] The second metal layer 33A is made of Pd or Au, and is preferably made of Pd from the viewpoint of further improving connection reliability. That is, the conductive particle 3A has a layer made of Au or Pd on the outermost surface of the conductive particle 3A, and is preferably made of Pd from the viewpoint of further improving reliability. The thickness of the second metal layer 33A may be, for example, 2 nm or more, 5 nm or more, or 10 nm or more, and may be 200 nm or less, 100 nm or less, or 50 nm or less.

[0033] The average particle size (diameter) of the conductive particles 3A may be preferably 1 μm or more and may be 100 μm or less. From the viewpoint of high-density mounting, the average particle size (diameter) of the conductive particles 3A may more preferably be 50 μm or less. From the viewpoint of maintaining a more stable connection state when there is variation in the surface unevenness of the electrodes, the average particle size (diameter) of the conductive particles 3A may further preferably be 2 μm or more or 3 μm or more, and may be 30 μm or less or 20 μm or less.

[0034] In this specification, the average particle size of the polymer particles and the average particle size of the conductive particles are defined as the average particle size values ​​obtained by measuring the particle size (diameter) of 300 polymer particles and 300 conductive particles in the adhesive composition by observation with a scanning electron microscope (SEM).

[0035] The thicknesses of the first metal layer 32A and the second metal layer 33A refer to the thicknesses of the metal layers at the portions where protrusions, which will be described later, are not formed. The thicknesses of the first metal layer 32A and the second metal layer 33A are defined as the average thicknesses obtained by measuring the thicknesses of the first metal layer and the second metal layer by observing 300 conductive particles in the adhesive composition using a scanning electron microscope (SEM).

[0036] In another embodiment, protrusions may be formed on the surface of the conductive particle 3. As shown in Fig. 2(b), a conductive particle 3B according to another embodiment has a substantially spherical polymer particle 31, a first metal layer 32B provided on the polymer particle 31, and a second metal layer 33B provided on the first metal layer 32B, and a plurality of protrusions 34 are formed on the surface of the conductive particle 3B. Hereinafter, the conductive particle 3B will be described, but since the conductive particle 3B has the same configuration as the conductive particle 3A shown in Fig. 2(a) except that the conductive particle 3B has the protrusions 34, a description of the common configuration will be omitted.

[0037] In the conductive particle 3B, the protrusion 34 is composed of the first metal layer 32B and the second metal layer 33B. From the viewpoint of further improving the connection reliability, the height of the protrusion 34 is preferably 60 nm or more, 90 nm or more, or 100 nm or more, and preferably 1200 nm or less, 600 nm or less, 400 nm or less, or 200 nm or less.

[0038] Here, the height of the protrusion 34 is determined by analyzing a two-dimensional image including a projected image of the conductive particles. The analysis of the two-dimensional image can be performed according to the method described in JP 2016-61722 A.

[0039] Specifically, for example, the protrusion height can be determined by a method including the steps of: detecting particle edges, which are the boundaries between the projected images of each conductive particle and other areas in a two-dimensional image in which a plurality of conductive particles are captured; calculating the central coordinates of the conductive particles on the two-dimensional image based on the particle edges; dividing the particle edges into a plurality of particle edge portions (e.g., 12 portions) at predetermined angles around the central coordinates, calculating the difference between the maximum and minimum values ​​of the distance between the central coordinates and the particle edge for each of the plurality of particle edge portions, and calculating the average value of these differences as the protrusion height; and calculating the average value of the protrusion heights calculated for a plurality of conductive particles (e.g., any number of 5 to 100 particles).

[0040] In the analysis of the two-dimensional image, the particle edge substantially corresponds to the outer periphery of the two-dimensional projection image of the conductive particle, including the unevenness resulting from the protrusion. The frequency distribution of the luminance obtained from the two-dimensional image generally shows a minimum value reflecting the particle edge portion. The two-dimensional image is binarized using the luminance corresponding to this minimum value as a first threshold value to generate a binarized image. The edge formed in the obtained binarized image is detected as the particle edge. The central coordinates of the conductive particle on the two-dimensional image are calculated based on the particle edge. A circle fitting to the particle edge is found by the least squares method, and the center of the circle is taken as the central coordinates of the conductive particle.

[0041] From the viewpoint of further improving connection reliability, the area ratio of the protrusions 34 to the entire projected image of the surface of the conductive particle 3 (area ratio of the protrusions 34) is preferably 8% or more, 9% or more, 10% or more, or 20% or more, and is preferably 60% or less or 50% or less.

[0042] The area ratio of the protrusions can also be determined by analyzing a two-dimensional image of the conductive particles according to the method described in JP 2016-61722 A. The area ratio of the protrusions can be determined, for example, by a method including a step of calculating a second threshold value corresponding to the boundary between the protrusions and other parts from the frequency distribution of luminance in the area inside the particle edge, a step of binarizing the area inside the particle edge using the obtained second threshold value to generate a binarized image, and a step of calculating, in the obtained binarized image, the ratio of the area of ​​the area corresponding to the protrusions to the area inside the particle edge as the area ratio of the protrusions.

[0043] The conductive particles 3 as described above can be obtained, for example, by forming a first metal layer 32 and a second metal layer 33 by metal plating on the surface of a polymer particle 31. More specifically, for example, the first metal layer 32 is formed on the surface of the polymer particle 31 by metal plating, and then a layer of Au or Pd is formed by displacement plating to obtain the second metal layer 33.

[0044] 2(b), the protrusions 34 can be formed by changing the plating conditions during metal plating to vary the thicknesses of the first metal layer 32 and the second metal layer 33. More specifically, for example, the concentration of the plating solution can be gradually increased during the metal plating process to form the protrusions 34.

[0045] Since the conductive particles 3 described above have a second metal layer 33 formed of Pd or Au on the outermost surface of the conductive particles 3, it becomes possible to obtain a more reliable electrical connection when an adhesive composition (adhesive film 1) containing these conductive particles 3 is used to connect a circuit component (described in detail below) whose electrode to be connected has a layer formed of Cu or Ag on its outermost surface.

[0046] The content of the conductive particles 3 contained in the adhesive film 1 is determined according to the fineness of the electrodes to be connected, etc. The content of the conductive particles 3 may be, for example, 1 part by mass or more and 200 parts by mass or less per 100 parts by mass of the adhesive component, and from the viewpoints of insulation properties and production costs, it may be preferably 100 parts by mass or less and 50 parts by mass or less.

[0047] The adhesive composition may contain only the conductive particles 3 described above as conductive particles, or may further contain conductive particles other than the conductive particles 3 described above (hereinafter also referred to as "other conductive particles"). The other conductive particles may be, for example, dendritic (also called arborescent) conductive particles. The dendritic conductive particles have one main axis and a plurality of branches branching two-dimensionally or three-dimensionally from the main axis. The dendritic conductive particles may be made of a metal such as copper or silver, and may be, for example, silver-coated copper particles obtained by coating copper particles with silver.

[0048] Specifically, the dendritic conductive particles are available as ACBY-2 (Mitsui Mining & Smelting Co., Ltd.), CE-1110 (Fukuda Metal Foil & Powder Co., Ltd.), #FSP (JX Metals Corporation), and #51-R (JX Metals Corporation). Alternatively, the dendritic conductive particles can be produced by a known method (for example, the method described in WO 2014 / 021037).

[0049] The other conductive particles may be, in addition to dendritic conductive particles, needle-shaped conductive particles (e.g., needle-shaped conductive particles made of silver-coated potassium titanate fibers (available as YTA-1575 (YCC Yokosawa Metal Industry Co., Ltd.))), amorphous conductive particles (e.g., amorphous conductive particles made of copper-coated graphite (available as CC-13D (YCC Yokosawa Metal Industry Co., Ltd.))), etc.

[0050] The content of the other conductive particles may be, for example, 5 parts by mass or more and 100 parts by mass or less with respect to 100 parts by mass of the adhesive component.

[0051] The adhesive composition may be in the form of a multilayer film (multilayer adhesive film). The multilayer adhesive film may be, for example, a two-layer structure consisting of a layer containing conductive particles and a layer not containing conductive particles, or a three-layer structure consisting of a layer containing conductive particles and layers not containing conductive particles provided on both sides of the layer containing conductive particles. The multilayer adhesive film may have a plurality of layers containing conductive particles. In consideration of the adhesiveness with the circuit members, the multilayer adhesive film may have an adhesive layer that exhibits high adhesiveness to the circuit members to be connected. When these multilayer adhesive films are used, the conductive particles can be efficiently captured on the connection electrodes, which is advantageous for connecting circuit members with narrow pitches.

[0052] The adhesive composition (adhesive film) described above is preferably used as a material (circuit connecting material) for connecting circuit components together, and more specifically, is particularly preferably used as an anisotropic conductive adhesive composition (anisotropic conductive adhesive film) or an isotropic conductive adhesive composition (isotropic conductive adhesive film) for connecting circuit components together.

[0053] Next, a method for manufacturing a connection structure using the adhesive film 1 will be described. FIG. 3 is a cross-sectional view that typically shows a method for manufacturing a connection structure according to one embodiment. First, as shown in FIG. 3(a), a first circuit member 4, a second circuit member 5, and an adhesive film 1 (circuit connecting material) are prepared. The first circuit member 4 has a first substrate 6 and a first electrode 7 provided on one surface 6a of the first substrate 6. The second circuit member 5 has a second substrate 8 and a second electrode 9 provided on one surface 8a of the second substrate 8.

[0054] Next, the first circuit member 4 and the second circuit member 5 are arranged so that the first electrode 7 and the second electrode 9 face each other, and an adhesive film 1 is placed between the first circuit member 4 and the second circuit member 5 to prepare a laminate.

[0055] The adhesive film 1 is cured while applying pressure to the entire laminate in the direction indicated by the arrow in FIG. 3(a). The pressure during application of pressure may be, for example, 1 to 10 MPa per total connection area. The adhesive film 1 may be cured by heating, or may be cured by combining heating with light irradiation. Heating may be performed at, for example, 100 to 170°C. Pressurization and heating (and light irradiation as necessary) may be performed for, for example, 1 to 160 seconds. As a result, the first circuit member 4 and the second circuit member 5 are pressure-bonded via the cured product of the adhesive composition constituting the adhesive film 1.

[0056] In the above embodiment, the adhesive film 1 is disposed between the first circuit member 4 and the second circuit member 5. However, in another embodiment, instead of the adhesive film, a paste-like adhesive composition may be applied to one or both of the first circuit member 4 and the second circuit member 5.

[0057] As shown in FIG. 3(b), the connection structure 10 according to one embodiment thus obtained includes a first circuit member 4 having a first substrate 6 and a first electrode 7 provided on the first substrate 6, a second circuit member 5 having a second substrate 8 and a second electrode 9 provided on the second substrate 8, and a connection portion 11 provided between the first circuit member 4 and the second circuit member 5, electrically connecting the first circuit member 4 (first electrode 7) and the second circuit member 5 (second electrode 9) to each other. The connection portion 11 is made of a cured product of the adhesive composition, and is made of a cured product 12 of the adhesive component 2 and conductive particles 3 dispersed in the cured product 12. In the connection structure 10, the conductive particles 3 are interposed between the first electrode 7 and the second electrode 9, so that the first electrode 7 and the second electrode 9 are electrically connected to each other.

[0058] The first substrate 6 may be, for example, an IC chip or a flexible substrate. The second substrate 8 may be, for example, a flexible substrate, a glass substrate, or a composite substrate having a glass substrate and an insulating film provided on the glass substrate.

[0059] More specifically, as a combination of the first substrate 6 and the second substrate 8, the first substrate 6 may be an IC chip or a flexible substrate, and the second substrate 8 may be a flexible substrate. Alternatively, the first substrate 6 may be an IC chip or a flexible substrate, and the second substrate 8 may be a glass substrate or a composite substrate. In other words, when the second substrate 8 is a flexible substrate, the first substrate 6 may be an IC chip or a flexible substrate. When the first substrate 6 is an IC chip and the second substrate 8 is a flexible substrate, the above-mentioned adhesive film 1 is used for COP (Chip on Plastic substrate) connection. When the first substrate 6 and the second substrate 8 are flexible substrates, the above-mentioned adhesive film 1 is used for FOP (Film on Plastic substrate) connection.

[0060] The flexible substrate contains, for example, at least one thermoplastic resin selected from the group consisting of polyimide (PI), polyethylene terephthalate (PET), polycarbonate (PC), and polyethylene naphthalate (PEN).

[0061] The flexible substrate may further have a modification treatment film such as a hard coat and / or a protective film formed on the surface of the organic substrate to improve optical and mechanical properties. In order to facilitate handling and transportation of the flexible substrate, a reinforcing material selected from a glass substrate, SUS, etc. may be bonded to the organic substrate.

[0062] The thickness of the flexible substrate may be 10 μm or more, and may be 200 μm or less, or 125 μm or less, in order to ensure the strength and bendability of the substrate alone as a film.

[0063] The glass substrate may be made of soda glass, quartz glass, or the like, and may be a substrate that has been subjected to a chemical strengthening treatment in order to prevent damage due to external stress. The composite substrate may have a glass substrate and an insulating film made of polyimide or an organic or inorganic material that is colored for decoration and provided on the surface of the glass substrate, and in the composite substrate, the electrodes may be formed on the insulating film.

[0064] When the second substrate 8 is a flexible substrate, the first substrate 6 may be an electronic component such as an active element such as a semiconductor chip, a transistor, a diode, a thyristor, or a passive element such as a capacitor, a resistor, a coil, or a printed circuit board, etc. When the first substrate 6 is an IC chip, a bump formed by plating or the tip of a gold wire is melted with a torch or the like to form a gold ball, and the ball is pressed onto an electrode pad, and then a protruding electrode (first electrode 7) such as a wire bump obtained by cutting the wire is provided, and this can be used as the first circuit member 4.

[0065] The first electrode 7 and the second electrode 9 may be formed of, for example, a metal such as Ag, Ni, Al, Au, Cu, Sn, Ti, or Mo, or a metal oxide such as ITO or IZO. The first electrode 7 and the second electrode 9 may be formed of the same material or different materials. The first circuit member 4 and the second circuit member 5 may each be provided with one first electrode 7 or one second electrode 9, but preferably a large number of electrodes are provided at predetermined intervals.

[0066] At least one of the first electrode 7 and the second electrode 9 has a layer formed of Cu or Ag on the outermost surface of the electrode, and preferably, only one of the first electrode 7 and the second electrode 9 has a layer formed of Cu or Ag on the outermost surface of the electrode. In one embodiment, the first electrode 7 may have a layer formed of Sn on the outermost surface of the electrode, and the second electrode 9 may have a layer formed of Cu on the outermost surface of the electrode, the first electrode 7 may have a layer formed of Cu on the outermost surface of the electrode, and the second electrode 9 may have a layer formed of ITO on the outermost surface of the electrode, or the first electrode 7 may have a layer formed of Sn or Au on the outermost surface of the electrode, and the second electrode 9 may have a layer formed of Ag on the outermost surface of the electrode.

[0067] By using the above-mentioned circuit connection material (adhesive film), a more reliable electrical connection can be obtained even when at least one of the first electrode 7 and the second electrode 9 has a layer formed of Cu or Ag on the outermost surface of the electrode. EXAMPLES

[0068] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.

[0069] [Example 1] <Synthesis of polyurethane acrylate (UA1)> Into a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser having a calcium chloride drying tube, and a nitrogen gas inlet tube, 2500 parts by mass (2.50 mol) of poly(1,6-hexanediol carbonate) (trade name: Duranol T5652, manufactured by Asahi Kasei Chemicals Corporation, number average molecular weight 1000) and 666 parts by mass (3.00 mol) of isophorone diisocyanate (manufactured by Sigma-Aldrich Co.) were uniformly dropped over 3 hours. Next, after sufficient nitrogen gas was introduced into the reaction vessel, the inside of the reaction vessel was heated to 70 to 75°C to cause a reaction. Next, 0.53 parts by mass (4.3 mmol) of hydroquinone monomethyl ether (Sigma-Aldrich) and 5.53 parts by mass (8.8 mmol) of dibutyltin dilaurate (Sigma-Aldrich) were added to the reaction vessel, and then 238 parts by mass (2.05 mol) of 2-hydroxyethyl acrylate (Sigma-Aldrich) were added and reacted at 70°C for 6 hours under air atmosphere. This resulted in polyurethane acrylate (UA1). The weight average molecular weight (Mw) of polyurethane acrylate (UA1) was 15,000. The weight average molecular weight was measured by gel permeation chromatography (GPC) using a calibration curve based on standard polystyrene under the following conditions.

[0070] (Measurement conditions) Equipment: Tosoh Corporation GPC-8020 Detector: Tosoh RI-8020 Column: Gelpack GLA160S+GLA150S manufactured by Hitachi Chemical Co., Ltd. Sample concentration: 120mg / 3mL Solvent: Tetrahydrofuran Injection volume: 60μL Pressure: 2.94×10 6 Pa(30kgf / cm 2 ) Flow rate: 1.00mL / min

[0071] <Preparation of conductive particles 1> A layer of nickel (Ni) was formed on the surface of polystyrene particles with an average particle size of 5 μm to a thickness of 100 nm, and a layer of palladium (Pd) was further formed on the surface as a second metal layer to a thickness of 20 nm. 3 ) Conductive particles 1 were obtained.

[0072] <Preparation of film-like adhesive composition (adhesive film)> The following components were mixed in the following amounts (parts by mass), and then the above-mentioned conductive particles 1 were mixed in an amount of 5 parts by mass per 100 parts by mass of the total solid content (adhesive components) other than the conductive particles of the adhesive composition to obtain a varnish of the adhesive composition. Next, the varnish of the adhesive composition was applied to a PET film having a thickness of 50 μm using a coating device. Then, hot air drying was performed at 70° C. for 3 minutes to produce an adhesive film having a thickness of 14 μm on the PET film.

[0073] (Radical polymerizable compound) Bis(acryloxyethyl) isocyanurate (product name: M-215, manufactured by Toagosei Co., Ltd.): 15 parts by weight Polyurethane acrylate (UA1) synthesized as described above: 32.5 parts by weight 2-Methacryloyloxyethyl acid phosphate (product name: Light Ester P-2M, manufactured by Kyoeisha Chemical Co., Ltd.): 1.5 parts by mass (Radical polymerization initiator) Benzoyl peroxide (product name: Niper BMT-K40, manufactured by NOF Corporation): 2.5 parts by weight (thermoplastic resin) Bisphenol A phenoxy resin (product name: PKHC, manufactured by Union Carbide): 42.5 parts by weight (Coupling Agent) 3-Methacryloxypropyltrimethoxysilane (product name: KBM503, manufactured by Shin-Etsu Chemical Co., Ltd.): 1 part by mass (filling material) Silica particles (product name: R104, manufactured by Nippon Aerosil Co., Ltd., average particle size (primary particle size): 12 nm): 5 parts by mass (solvent) Methyl ethyl ketone: 150 parts by weight

[0074] [Example 2] An adhesive film was produced in the same manner as in Example 1, except that conductive particles 2 produced as follows were used as the conductive particles.

[0075] <Preparation of conductive particles 2> Conductive particle 2 was prepared in the same manner as conductive particle 1, except that a layer of gold (Au) was formed to a thickness of 20 nm as the second metal layer instead of a layer of Pd.

[0076] [Example 3] An adhesive film was produced in the same manner as in Example 1, except that conductive particles 3 produced as follows were used as the conductive particles.

[0077] <Preparation of Conductive Particles 3> A layer of Ni was formed on the surface of polystyrene particles with an average particle size of 3 μm to a thickness of 100 nm, and a layer of Pd was further formed on the surface as a second metal layer to a thickness of 20 nm. 3 ) Conductive particles 3 were obtained.

[0078] [Example 4] An adhesive film was produced in the same manner as in Example 1, except that conductive particles 4 produced as follows were used as the conductive particles.

[0079] <Preparation of Conductive Particles 4> Conductive particle 4 was produced in the same manner as conductive particle 3, except that, as the second metal layer, a layer made of Au was formed to a thickness of 20 nm instead of the layer made of Pd.

[0080] [Comparative Example 1] An adhesive film was produced in the same manner as in Example 1, except that conductive particles 5 produced as follows were used as the conductive particles.

[0081] <Preparation of Conductive Particles 5> Conductive particle 5 was produced in the same manner as conductive particle 1, except that the second metal layer was not provided.

[0082] [Comparative Example 2] An adhesive film was produced in the same manner as in Example 1, except that conductive particles 6 produced as follows were used as the conductive particles.

[0083] <Preparation of Conductive Particles 6> Conductive particle 6 was produced in the same manner as conductive particle 3, except that the second metal layer was not provided.

[0084] <Preparation of connection structure> The adhesive films of the examples and comparative examples were used to prepare the following connection structures 1 to 5.

[0085] (Connection structure 1 (top electrode surface: Sn / Cu)) Each adhesive film (with PET film) of the examples and comparative examples was cut into a size of 1 mm wide x 4 cm long. In addition, a circuit member A1 (top electrode surface: Cu) was prepared on a glass substrate, in which electrodes of titanium (film thickness 50 nm) and copper (film thickness 500 nm) were provided in this order. Next, the adhesive film on the PET film was transferred onto this circuit member (so as to cover the electrodes). The transfer conditions were 70°C, 1 MPa, and 2 seconds. After that, the PET film was peeled off to expose the adhesive film, and a flexible circuit member B1 (FPC, top electrode surface: Sn) having 150 tin-plated copper circuits with a pitch of 200 μm and a thickness of 8 μm on a polyimide substrate was temporarily fixed to the adhesive film, thereby obtaining a temporarily fixed structure. The temporary fixing conditions were 24°C, 0.5 MPa, and 1 second. Next, the temporarily fixed structure was placed in a permanent bonding device, and a 200 μm thick silicone rubber sheet was used as a cushioning material, and the FPC side was heated and pressurized at 140° C. and 2 MPa for 10 seconds using a heat tool to connect over a width of 1 mm. This resulted in a connection structure.

[0086] (Connection structure 2 (top electrode surface: Cu / ITO)) Connection structure 2 was obtained in the same manner as connection structure 1, except that circuit member A2 (top electrode surface: ITO) having an ITO (film thickness 100 nm) electrode on a glass substrate was used instead of circuit member A1, and flexible circuit member B2 (FPC, top electrode surface: Cu) having 150 copper circuits with a pitch of 200 μm and a thickness of 8 μm on a polyimide substrate was used instead of flexible circuit member B1.

[0087] (Connection structure 3 (top electrode surface: Au / Cu)) Connection structure 3 was obtained in the same manner as connection structure 1, except that circuit member A3 (top electrode surface: Cu) having a Cu electrode (film thickness 500 nm) provided on a PET substrate was used instead of circuit member A1, and flexible circuit member B3 (FPC, top electrode surface: Au) having 150 gold-plated copper circuits with a pitch of 200 μm and a thickness of 12 μm on a polyimide substrate was used instead of flexible circuit member B1.

[0088] (Connection structure 4 (top electrode surface: Au / Ag)) Connection structure 4 was obtained in the same manner as connection structure 1, except that circuit member A4 (top electrode surface: Ag) having an electrode (film thickness 10 μm) formed from Ag paste on a PET substrate was used instead of circuit member A1, and flexible circuit member B3 (FPC, top electrode surface: Au) was used instead of flexible circuit member B1.

[0089] (Connection structure 5 (top electrode surface: Sn / ITO)) Connection structure 5 was obtained in the same manner as connection structure 1, except that circuit member A2 (outer electrode surface: ITO) was used instead of circuit member A1.

[0090] <Evaluation of connection reliability> The resulting connection structures were subjected to a reliability test at 85° C., 85% RH, and 500 hours. The connection resistance (Ω) between the opposing circuit members of the connection structures was measured before and after the test. The results are shown in Table 1.

[0091] [Table 1]

[0092] When the outermost surface of the electrode in at least one of the circuit members was made of Cu or Ag (Connection Structures 1-4), the use of adhesive films (Examples 1-4) containing conductive particles 1-4 whose outermost surface was made of Pd or Au provided more reliable electrical connections than the use of adhesive films (Comparative Examples 1 and 2) containing conductive particles 5 and 6 whose outermost surface was made of Ni. On the other hand, when the outermost surface of the electrode in the circuit member was made of a metal other than Cu and Ag (Connection Structure 5), no difference in connection resistance due to the type of the outermost surface of the conductive particles as described above was observed. [Explanation of symbols]

[0093] 1...adhesive film, 2...adhesive component, 3...conductive particles, 4...first circuit member, 5...second circuit member, 6...first substrate, 7...first electrode, 8...second substrate, 9...second electrode, 10...connection structure, 11...connection portion, 31...polymer particles, 32, 32A, 32B...first metal layer, 33, 33A, 33B...second metal layer, 34...protrusion portion.

Claims

1. a first circuit member having a first electrode; a second circuit member having a second electrode; a connection portion provided between the first circuit member and the second circuit member, electrically connecting the first electrode and the second electrode to each other; At least one of the first electrode and the second electrode has a layer formed of Cu or Ag on its outermost surface, A connection structure, wherein the connection portion contains conductive particles having a layer formed of Pd or Au on the outermost surface.

2. The connection structure according to claim 1 , wherein the conductive particles have a layer formed of Pd on the outermost surface.

3. Contains an adhesive component and conductive particles, An adhesive composition used to bond a first circuit member having a first electrode and a second circuit member having a second electrode to each other, thereby electrically connecting the first electrode and the second electrode to each other, comprising: the conductive particles have a layer formed of Pd or Au on their outermost surface, At least one of the first electrode and the second electrode has a layer formed of Cu or Ag on its outermost surface.

4. The adhesive composition according to claim 3 , wherein the conductive particles have a layer formed of Pd on the outermost surface.

Citation Information

Patent Citations

  • Conductive particle, anisotropic conductive adhesive, and connection structure

    JP2016181511A